Displacing human rights : war and intervention in northern Uganda - Branch, Adam, 1975- (New York ; Oxford : Oxford University Press, 2011)
This title lays bare the reductive understandings motivating Western intervention in Africa, the inadequate tools it insists on employing, its refusal to be accountable to African citizenries, and, most important, its counterproductive consequences for peace, human rights, and justice.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Human rights -- Uganda; Civil rights -- Uganda; Humanitarian intervention -- Uganda; War and society -- Uganda; Uganda -- Politics and government; Uganda -- Social conditions